At1 receptor blockade improves myocardial functional performance in obesity - de Oliveira-Junior, Silvio Assis; Muzili, Nayara de Araújo; Carvalho, Marianna Rabelo de; Ota, Gabriel Elias; de Morais, Camila Souza; Vieira, Larissa Fregapani da Costa; Ortiz, Mateus Oliveira; Campos, Dijon H. S. [UNESP]; Cezar, Marcelo Diacardia Mariano [UNESP]; Okoshi, Marina Politi [UNESP]; Okoshi, Katashi [UNESP]; Cicogna, Antonio C. [UNESP]; et al. (Sociedade Brasileira de Cardiologia, 2020)
Background: Obesity has been associated with chronic activation of the renin-angiotensin-aldosterone system and with significant changes in cardiac performance. Objective: To assess the impact of a blockade of angiotensin-II receptor type 1 (AT1 receptor) on morphology and on myocardial functional performance in rats with high-fat diet-induced obesity. Methods: Wistar rats (n=48) were submitted to control (2.9 kcal/g) or high-fat (3.6 kcal/g) diet for 20 weeks. After the 16th week they were divided into four groups: Control (CO), Obese (OB), Control Losartan (CL) and Obese Losartan (OL). CL and OL received losartan (30 mg/kg/day) in drinking water for four weeks. Subsequently, body composition, systolic blood pressure (SBP) and echocardiographic variables were analyzed. Papillary muscle function was assessed at baseline with 2.50 mM calcium concentration ([Ca2+] ) and after inotropic maneuvers: post-pause potentiation (PPP), [Ca2+]o elevation, and during beta-adrenergic stimulationo with isoproterenol. Analysis of the results was performed by the Two-Way ANOVA and by the appropriate comparison test. The level of significance was set at 5%. Results: Although SBP change had been not maintained at the end of the experiment, obesity was associated with cardiac hypertrophy and with increased left ventricle posterior wall shortening velocity. In the study of papillary muscles in basal condition, CL showed lower developed tension maximum negative variation velocity (-dT/dt) than CO. The 60s PPP promoted lower-dT/dt and maximum developed tension (DT) in OB and CL compared with CO, and higher relative DT variation and maximum positive variation velocity (+dT/dt) in OL compared with CL and OB. Under 1.5, 2.0, and 2.5mM [Ca2+]o, the OL group showed higher-dT/dt than CL. Conclusion: Losartan improves myocardial function in high-fat diet-induced obesity.
Bloqueio de Receptores AT1 Melhora o Desempenho Funcional Miocárdico na Obesidade
Keywords: Angiotensin II Type 1 Receptor Blockers/ therapeutic use; Cardiovascular Diseases; Diet, High-fat/methods; Losartan/therapeutic use; Obesity; Rats